Financial risk aversion and household asset diversification - Nataliya Barasinska; Dorothea Schäfer; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper explores the relationship between risk attitude and asset diversification in household portfolios. We first examine the impact of manifested risk aversion on the total number of distinct assets held in a portfolio (naive diversification). The second part of the paper focuses on a more sophisticated strategy of diversification and asks whether financial theory is compatible with observed diversification patterns. Based on the German Socioeconomic Panel which provides unique measures of individual propensity for taking risk, the results of the regression analysis show that, along with some socioeconomic characteristics, the propensity for taking investment risk is an important predictor of a household's diversification strategy. However, some of our findings are strongly at odds with what the concept of mean-variance utility suggests.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: D14; G11; 330; household finances; diversification; financial portfolio; Privater Haushalt; Anlageverhalten; Portfolio-Management; Risikoaversion; Deutschland